The Effect of Brainstorming on Students’ Creative Thinking Skill in Learning Nutrition - Winda Ismi Hidayanti; Diana Rochintaniawati; Rika Rafikah Agustin (Journal of Science Learning, 2018)
This research investigated the effect of brainstorming on students’ creative thinking skills in learning nutrition. The method that was used in this research is quasi-experimental with a pretest-posttest design. The sample was taken by purposive sampling technique where one group was assigned to the experimental group (n=25 students) and the other one group was assigned to the control group (n=25 students). The population was 7th-grade students in Islamic International School in Bandung. The quantitative data in this research was obtained from objective test and verbal TTCT (Torrance Test of Creative Thinking), while the qualitative data was obtained from observation sheet. The findings of the study showed that there are statistically significant differences between experimental and control group in creative thinking skills test with the score of 0.000. The result is in the favor of the experimental group, indicating the effectiveness of brainstorming in developing students’ creative thinking skills in learning nutrition.